Conservation status assessment of Scolopendromorpha (Chilopoda) species in Chile - Emmanuel Vega-Román; Gonzalo A. Collado; Jaime Pizarro-Araya (Zoologia (Curitiba), 2025)
ABSTRACT This study presents the first assessment of the conservation status of Chilean species of the order Scolopendromorpha, a group rarely included in conservation policies. Eleven species were identified (three from Akymnopellis and eight from Cryptops) through a literature review and databases such as CHILOBASE and GBIF. IUCN and NatureServe criteria were applied, estimating the extent of occurrence (EOO) and area of occupancy (AOO) using tools like GeoCAT. Results indicate that all species face some degree of threat, with Cryptops armatus Silvestri, 1899, Cryptops detectus Silvestri, 1899, Cryptops nahuelbuta Chamberlin, 1955, and Cryptops triserratus Attems, 1903 classified as critically endangered. The most frequent threats include urbanization, deforestation, and land use change. The discussion highlights the urgent need to include these species in official conservation lists, promote research on their biology, and propose measures such as the creation of microreserves and environmental education programs, given their limited distribution, ecological vulnerability, and ecological importance.